Climate change mitigation and improvement of water quality from the restoration of a subtropical coastal wetland. Issue 5 (23rd May 2022) - Iram, Naima; Maher, Damien T.; Lovelock, Catherine E.; Baker, Tallis; Cadier, Charles; Adame, Maria F.
Abstract: Coastal wetland restoration is an important activity to achieve greenhouse gas (GHG) reduction targets, improve water quality, and reach the Sustainable Development Goals. However, many uncertainties remain in connection with achieving, measuring, and reporting success from coastal wetland restoration. We measured levels of carbon (C) abatement and nitrogen (N) removal potential of restored coastal wetlands in subtropical Queensland, Australia. The site was originally a supratidal forest composed of Melaleuca spp. that was cleared and drained in the 1990s for sugarcane production. In 2010, tidal inundation was reinstated, and a mosaic of coastal vegetation (saltmarshes, mangroves, and supratidal forests) emerged. We measured soil GHG fluxes (CH4, N2 O, CO2 ) and sequestration of organic C in the trees and soil to estimate the net C abatement associated with the reference, converted, and restored sites. To assess the influence of restoration on water quality improvement, we measured denitrification and soil N accumulation. We calculated C abatement of 18.5 Mg CO2−eq ha −1 year −1 when sugarcane land transitioned to supratidal forests, 11.0 Mg CO2−eq ha −1 year −1 when the land transitioned to mangroves, and 6.2 Mg CO2−eq ha −1 year −1 when the land transitioned to saltmarshes. The C abatement was due to tree growth, soil accumulation, and reduced N2 O emissions due to the cessation of fertilization. Carbon abatement was still positive, even accounting for CH4 emissions, which increased in the wetlands due to flooding and N2 O production due to enhanced levels of denitrification. Coastal wetland restoration in this subtropical setting effectively reduces CO2 emissions while providing additional cobenefits, notably water quality improvement.